Streptococcal Pyrogenic Exotoxin B-Induced Apoptosis in A549 Cells Is Mediated through α(v)β(3) Integrin and Fas - Tsai, Wan-Hua (American Society for Microbiology (ASM), 2008)
Our previous work suggested that streptococcal pyrogenic exotoxin (SPE) B-induced apoptosis is mediated through a receptor-like mechanism. In this study, we have identified α(v)β(3) and Fas as the SPE B receptors for this function. The SPE B fragment without the RGD motif and G308S, a SPE B mutant with the RSD motif, induced less apoptosis than did native SPE B, suggesting that the RGD motif is critical for SPE B-induced apoptosis. Fluorescein isothiocyanate-SPE B binding assays and immunoprecipitation analysis showed that SPE B specifically interacted with α(v)β(3). Anti-α(v)β(3) antibody partially inhibited SPE B-induced apoptosis but had no effect on G308S-induced apoptosis. In addition, Fas binding to SPE B was verified in an affinity column and an immunoprecipitation analysis. Anti-Fas antibody inhibited SPE B- and G308S-induced apoptosis in a dose-dependent manner, suggesting that Fas-mediated SPE B-induced apoptosis also occurs RGD independently. Both anti-α(v)β(3) and anti-Fas antibodies synergistically inhibited SPE B-induced apoptosis. The apoptotic cascades were activated by SPE B and G308S, with a little delay by the latter. After SPE B binding, the cell surface level of α(v)β(3), but not of Fas, was decreased. The decreased α(v)β(3) level was restored by treatment with the proteasome inhibitor MG132, suggesting a SPE B-mediated endocytosis of integrin α(v)β(3) via the ubiquitin-proteasome system. Taken together, our results demonstrate that SPE B-induced apoptosis is mediated through α(v)β(3) integrin and Fas in a synergistic manner.